2018
DOI: 10.1051/matecconf/201824300024
|View full text |Cite
|
Sign up to set email alerts
|

Structure and mechanical properties of A356-C alloys

Abstract: The paper deals with influence of mechanical mixing and vibration treatment on the structure and mechanical characteristics of the aluminum alloy containing ≤ 1 wt.% of nanodiamonds (A356-C). The alloy was obtained from industrial A356 Al-Si casting alloy by means of an integrated effect of mechanical mixing and vibration. It has been shown that the introduction of nanodiamond particles contributes to improving the alloy structure and increasing its mechanical tensile properties. The structure of the A356 alum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…The alloy demonstrated a highly efficient use of ScF 3 -based modifiers and additional ultrasonic treatment. The mechanical mixing and vibration treatment used in [16] affected the structure and mechanical properties of the aluminum alloy A356-C consisting of ≤1 wt.% nanodiamonds. It was shown that the yield strength and ultimate stress limit (USL) of the A356 alloy increased without changing its plasticity.…”
Section: Introductionmentioning
confidence: 99%
“…The alloy demonstrated a highly efficient use of ScF 3 -based modifiers and additional ultrasonic treatment. The mechanical mixing and vibration treatment used in [16] affected the structure and mechanical properties of the aluminum alloy A356-C consisting of ≤1 wt.% nanodiamonds. It was shown that the yield strength and ultimate stress limit (USL) of the A356 alloy increased without changing its plasticity.…”
Section: Introductionmentioning
confidence: 99%